GAMBARAN PENGETAHUAN REMAJA MENGENAI BAHAYA HAMIL USIA DINI PADA SISWI DI SMA SEI PUTIH KECAMATAN TAPUNG KABUPATEN KAMPAR TAHUN 2021 - Lora Marlita; Andalia Roza; Ariana Dewi (STIKes Al-Insyirah Pekanbaru, 2021)
ABSTRACT Pregnancy is the fertilization or fusion of spermatozoa and ovum followed by bullying or implantation. It can be calculated from the time of fertilization to the birth of the baby, a normal pregnancy will last within 40 weeks. The purpose of this study was to determine the description of adolescent knowledge regarding the dangers of early pregnancy in SMA Sei Putih, Tapung District, Kampar Regency in 2021. Using this type of quantitative descriptive research. The population in this study were 52 Sei Putih high school students. The sampling technique in this study used a quota sampling technique where the researcher took the sample according to the target or desired. The research instrument used a Guttman scale questionnaire consisting of 20 questions. Data analysis used univariate analysis. It is known that the level of knowledge in this study is sufficient by the number of 28 respondents (53.84%) Keywords: Pregnancy, Schoolgirl, Early Childhood Pregnancy Hazard